(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The choice of technologies for mechanical processing of details is closely related to the requirements toward dimensional accuracy, shape and mutual position of their surfaces, which are set by the constructor. Wrong dimensioning in many cases leads to complications and raising the cost of mechanical processing. The present paper makes a comparative analysis of different options for dimensioning a stepped shaft, machined on a CNC lathe. Recommendations for purposeful dimensioning of similar details are made based on the above-mentioned analysis.